The Abstract: the letter of presentation for a scientific paper - Camps, Diego Eduardo (2010)
The abstract is a part of scientific articles placed at the beginning of such. It guides us quickly and accurately about the information we will find in the complete manuscript. It must be written by selecting the appropriate words and sentences to achieve consistent, clear, and concise contents. We can group the abstract into two types according to their content: the descriptive abstract, which guides the reader regarding the contents of the article but requires reading the full text for further details; and the informative abstract, which condenses the study and provides accurate data about the contents of the paper. The abstract has become a fundamental part of the scientific article, especially with the explosive growth of information; an adequate and well-built abstract allows scientists and researchers to recognize the work done by its authors. Attention should be dedicated to its construction because the success of our publication depends upon the very abstract